1972
DOI: 10.1073/pnas.69.7.1892
|View full text |Cite
|
Sign up to set email alerts
|

Role of DNA and Specific Cytoplasmic Receptors in Glucocorticoid Action

Abstract: Glucocorticoids induce tyrosine aminotransferase (EC 2.6.1.5) synthesis in cultured rat hepatoma cells. These steroids penetrate the cell membrane and bind to specific cytoplasmic receptor proteins. The resulting complex binds to the nucleus. This nuclear binding has nowlbeen studied in a cell-free preparation. The reaction appears to require a temperature-dependent modification of the steroid-receptor complex. There is a fixed number of nuclear sites that are half saturated at a complex concentration of 6 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…This is consistent with the observation that association with receptor is only the first of several steps between binding and biologic response (8). There is evidence that the receptor must undergo a temperature-dependent transformation after association with the steroid before uptake by the nucleus can occur (8,11,17,56,57), a step that does not occur with progesterone and cortexolene (8,10). Such steroids have therefore been termed "anti-inducers" (21).…”
Section: The Journal Of Clinical Investigation Volume 52 July 1973 17supporting
confidence: 62%
See 1 more Smart Citation
“…This is consistent with the observation that association with receptor is only the first of several steps between binding and biologic response (8). There is evidence that the receptor must undergo a temperature-dependent transformation after association with the steroid before uptake by the nucleus can occur (8,11,17,56,57), a step that does not occur with progesterone and cortexolene (8,10). Such steroids have therefore been termed "anti-inducers" (21).…”
Section: The Journal Of Clinical Investigation Volume 52 July 1973 17supporting
confidence: 62%
“…The binding of steroid hormones to highly specific, high affinity cytoplasmic receptor proteins has been suggested as the first step in steroid hormone action in many systems (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). These steroid-binding proteins (SBP)1 appear to be the determinant of target tissue specificity (4,6,7,12).…”
Section: Introductionmentioning
confidence: 99%
“…Whether the observed increase in cyclic AMP levels is due to increased adenyl cyclase activity, inhibition of phosphodiesterase, or a more indirect mechaism remains to be tested and is the subject of further investigation in this laboratory. Since the potentiation of PGEi-induced rises in cyclic AMP levels occurred within minutes, the mechanism is unrelated to the events associated with glucocorticosteroid-stimulated synthesis of specific proteins, which involves increased transcription of messenger RNA as a result of steroidreceptor complex binding to DNA (23). It should be stressed that the further stimulation of PGE,-induced increases in cyclic AMP levels does not account for the inhibitory effect of cortisol when added alone to peripheral lymphocyte cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Incubation of PHA-treated cultures with dibutyryl cyclic ANIP or Experiments were performed to determine the effects of PGE1 and cortisol, alone and in combination, upon lymphocyte cyclic AMP levels (Table III). Addition of 0.1 mM PGE1 resulted in a rapid elevation of intracellular cyclic AMP levels which peaked by [20][21][22][23][24][25][26][27][28][29][30] min, whereas at concentrations of 0.01-0.001 mMI PGE1, the response was variable. Cyclic ANIP levels rose 3.3±0.4- and with the combination of PGE1 plus cortisol.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases studied these effects are at the transcriptional level. Baxter et al (2) demonstrated that glucocorticoid-receptor complexes or proteins associated with them bind to DNA. It has been postulated that these complexes recognize specific sequences on responsive genes and affect their transcription (for reviews, see references 30 and 43).…”
mentioning
confidence: 99%